Nanoparticle Drones to Target Lung Cancer with Radiosensitizers and Cannabinoids - Ngwa, Wilfred; Kumar, Rajiv; Moreau, Michele; Dabney, Raymond; Herman, Allen (Frontiers in Oncology, 2017)
Nanotechnology has opened up a new, previously unimaginable world in cancer diagnosis and therapy, leading to the emergence of Cancer Nanomedicine and nanoparticle-aided radiotherapy. Smart nanomaterials (nanoparticle drones) can now be constructed with capability to precisely target cancer cells and be remotely activated with radiation to emit micrometer-range missile-like electrons to destroy the tumor cells. These nanoparticle drones can also be programmed to deliver therapeutic payloads to tumor sites to achieve optimal therapeutic efficacy. In this article we examine the state-of-the-art and potential of nanoparticle drones in targeting lung cancer. Inhalation (air) versus traditional intravenous (‘sea’) routes of navigating physiological barriers using such drones is assessed. Results and analysis suggest that inhalation route may offer more promise for targeting tumor cells with radiosensitizers and cannabinoids from the perspective of maximizing damage to lung tumors cells while minimizing any collateral damage or side effects.